High Nanopore Volume Tetrethoxysilane Based Aerogels Prepared with Addition of N, N-Dimethylformamide at Different Stage of the Sol-Gel Process - Chaoshuai LEI; Enshuang ZHANG; Hongyan HUANG; Xuyang JI; Lijuan HE; Wenjing LI; Jieying YANG; Yingmin ZHAO; Hao ZHANG (Medžiagotyra, 2021)
Using tetraethoxysilane (TEOS) as a precursor, silica aerogels were synthesized via the sol-gel polymerization followed by supercritical drying process. During the polymerization period, N, N-dimethylformamide (DMF), acting as a chemical additive for the structure control, was introduced in the hydrolysis step and condensation step, respectively. As a result, the nanopore volumes for the pores smaller than 100 nm were up to 6.0 cm3/g and 5.7 cm3/g for the samples that produced with DMF addition in the hydrolysis step and condensation step, while the value for the sample without DMF was only 4.6 cm3/g. Besides, the sample with DMF addition in the condensation step possessed more uniform pore size distribution while compared with that with DMF addition in the hydrolysis step. DMF can provide a shielding layer around the colloid particles through hydrogen bonds, inhibiting the aggregation of colloid particles and the enlarging of pore sizes.